A stylistic analysis of the columns of Conrado De Quiros - Satuito, Eleanor Vera (University of the Philippines Diliman, 1998)
"A Stylistic of the Columns of Conrado De Quiros" delved into the use , effect/s and implication/s of figurative language, metaphors in particular, in opinion column writing. The writing style of Conrado de Quiros was studied and analyzed in Lieu of one of M.A.K. Halliday's contributions to the study of English - a study on meaning. Through Halliday's interpersonal function, language is seen as a means of expression of the speaker or writer. In establishing the purpose and significance of the study, a collection of fifteen randomly chosen columns by Conrado de Quiros were read and analyzed through the identification of metaphor/s, tenor, communication role and other elements of writing style used by the writer.